TI_GERICHTE 90.2018.13 vom 29. November 2018 , Variante di piano regolatore - decisione di approvazione sospesa su alcuni aspetti - TI Tribunale d'appello (2018)
Variante di piano regolatore - decisione di approvazione sospesa su alcuni aspetti